2001
DOI: 10.1002/1439-7633(20010105)2:1<39::aid-cbic39>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of DNA Duplex Formation by Using Azobenzene-Bearing Oligonucleotides

Abstract: The duplex-forming activities of oligonucleotides can be photomodulated by incorporation of an azobenzene unit. Upon isomerizing the trans-azobenzene to the cis form by irradiation with UV light, the T(m) value of the duplex (with the complementary DNA) is lowered so that the duplex is dissociated. The duplex is formed again when the cis-azobenzene is converted to the trans-azobenzene by irradiation with visible light. The photoregulation is successful irrespective of the position of the azobenzene unit in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 4 publications
1
59
0
2
Order By: Relevance
“…Structural analysis revealed that the planar, nonpolar trans azobenzene moiety can intercalate more effectively in the duplex than the nonplanar, polar cis isomer. 152,153 The original azobenzene-containing a nucleotide unit was synthesized as a racemic mixture and the two diastereomeric forms had significantly different photoswitching behaviour. Subsequent synthesis of azobenzene containing phosphoramidites based on a D-threoninol backbone (24) gave enantiopure products with enhanced photoswitching ability.…”
Section: Photoswitchable Oligonucleotidesmentioning
confidence: 99%
“…Structural analysis revealed that the planar, nonpolar trans azobenzene moiety can intercalate more effectively in the duplex than the nonplanar, polar cis isomer. 152,153 The original azobenzene-containing a nucleotide unit was synthesized as a racemic mixture and the two diastereomeric forms had significantly different photoswitching behaviour. Subsequent synthesis of azobenzene containing phosphoramidites based on a D-threoninol backbone (24) gave enantiopure products with enhanced photoswitching ability.…”
Section: Photoswitchable Oligonucleotidesmentioning
confidence: 99%
“…When azobenzene molecules were intercalated at specific positions on DNA duplex, its helical binding stability could be easily disturbed by the polarity and conformational change of azobenzene under sequential irradiation of UV and visible light. It is experimentally confirmed that the overall binding stability of a DNA duplex is uniformly increased with increasing the number of trans ‐form azobenzene inserted . Upon UV light irradiation, trans ‐to‐ cis conversion of azobenzene whose biphenyl groups are on the same side of NN bond and form a nonplanar structure, disturbs the π–π stacking of nucleobase and destabilize the duplex formation.…”
Section: Design Of Photoresponsive Self‐assembled Dna Nanomaterials Vmentioning
confidence: 81%
“…Incorporation of azobenzene into DNA is another interesting way to control biological systems. In one case, the duplex of modified DNA could be reversibly switched (Asanuma et al, 2001), since the trans-azobenzene intercalates between base pairs and helps bind the two strands of the double helix together, whereas the cis-azobenzene disrupted the duplex (Liang et al, 2003). By incorporating an azobenzene unit into the promoter region of an otherwise normal DNA sequence, it was possible to photocontrol gene expression (Liu et al, 2005).…”
Section: Photobiological Experimentsmentioning
confidence: 99%
“…Azo-modified polypeptides can be photoswitched between ordered states (a-helix or b-sheet) and a random coil (Everlof and Jaycox, 2000;Fissi et al, 1996;Yamamoto and Nishida, 1991). The duplex of modified DNA can be reversibly switched (Asanuma et al, 2001), and the catalytic activity of histidine can be controlled (Lee and Ueno, 2001). …”
Section: Domain Motionmentioning
confidence: 99%